Lyotropic liquid crystal-assisted synthesis of micro- and nanoparticles of silver. Issue 9 (15th July 2017) - Umadevi, S.; Umamaheswari, R.; Ganesh, V.
ABSTRACT: A simple, one-step approach for the synthesis of micro- and nanoparticles of silver by employing a lyotropic liquid crystal (LLC) template is described. Anisotropic silver particles are synthesised by reducing an appropriate amount of precursor silver nitrate using a mild reducing agent ascorbic acid in presence of a hexagonal LLC medium, without the aid of any external stabilising agents. In this synthesis, precursor concentration, type of the reducing agent and LLC phase are found to significantly influence the particle size and morphology. Either a decrease in the concentration of silver nitrate or a change in the reducing agent, from ascorbic acid to sodium borohydride in the same reaction medium, yielded quasi-spherical nanoparticles. Besides, replacing the hexagonal LLC medium with a lamellar phase during the synthesis using ascorbic acid also resulted in the formation of spherical particles in nanometre scale. As a comparison, gold nanoparticle synthesis is carried out in hexagonal and lamellar LLC phases. Similar to the observations made in the silver particle synthesis, branched anisotropic particles are formed in the hexagonal phase and quasi-spherical particles are produced in the lamellar phase. A possible growth mechanism for the formation of these particles based on the phase structure of the LLC medium is discussed. GRAPHICAL ABSTRACT: